Effect of Deep Brain Stimulation on Regional Cerebral Blood Flow in Patients with Medically Refractory Tourette Syndrome - Haense, Cathleen; Müller-Vahl, Kirsten R.; Wilke, Florian; Schrader, Christoph; Capelle, Holger H.; Geworski, Lilli; Bengel, Frank M.; Krauss, Joachim K.; Berding, Georg (Frontiers in Psychiatry, 2016)
In this study alterations in brain perfusion have been investigated in patients with Tourette syndrome (TS) compared to control subjects. In addition, we investigated the effects of deep brain stimulation (DBS) in both globus pallidus internus (GPi) and centromedian-parafascicular / ventralis oralis internus nuclei of the thalamus (CM/Voi), and sham (SHAM) stimulation on cerebral blood flow. In a prospective controlled, randomized, double-blind setting 5 severely affected adult patients with TS with predominant motor or vocal tics (mean total tic score on the Yale Global Tic Severity Scale: 39) underwent serial brain perfusion single photon emission computed tomography (SPECT) with 99mTc-ECD. Results were compared with data from 6 age-matched control subjects. All patients were investigated at four different time points: once before DBS implantation (preOP) and three times postoperatively. Postoperative scans were performed in a randomized order each after 3 months of either GPi, CM/Voi, or SHAM stimulation. At each investigation, patients were injected at rest while awake, but scanned during anaesthesia. This procedure ensured that neither anaesthesia nor movement artefacts influenced our results. Control subjects were investigated only once at baseline (without DBS or anaesthesia). At baseline, cerebral blood flow was significantly reduced in patients with TS (preOP) compared to controls in the central region, frontal and parietal lobe, specifically in Brodmann areas 1, 4-9, 30, 31, and 40. Significantly increased perfusion was found in the cerebellum. When comparing SHAM stimulation to preOP condition, we found significantly decreased perfusion in basal ganglia and thalamus, but increased perfusion in different parts of the frontal cortex. Compared to SHAM condition both GPi and thalamic stimulation resulted in a significant decrease in cerebral blood flow in basal ganglia and cerebellum, while perfusion in the frontal cortex was significantly increased. Our results provide substantial evidence that in TS brain perfusion is altered in the frontal cortex and the cerebellum and that these changes can be reversed by both: GPi and CM/Voi DBS.